2011
DOI: 10.3390/ijerph8124502
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Indoor Air Pollution in Homes with Infants

Abstract: Infants spend most of their indoor time at home; however, residential air quality is poorly understood. We investigated the air quality of infants’ homes in the New England area of the U.S. Participants (N = 53) were parents of infants (0–6 months) who completed telephone surveys to identify potential pollutant sources in their residence. Carbon monoxide (CO), carbon dioxide (CO2), particulate matter with aerodynamic diameter ≤0.5 µm (PM0.5), and total volatile organic compounds (TVOCs) were measured in 10 hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
3
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 48 publications
0
31
3
3
Order By: Relevance
“…They found concentrations ranging from 2,000 to 56,000 count/cm 3 for indoor air in schools of the Cincinnati metropolitan area. Indoor total VOC levels measured in this investigation were fairly low compared to other studies conducted in the north-eastern US [210 – 6,000 μg/m 3 (Pickett et al, 2011)]. The indoor formaldehyde measurements also revealed somewhat lower levels than those reported by other investigators; Frey et al (2014) reported a median of 0.04 ppm in non-renovated homes and 0.05 ppm in renovated homes and Xiong et al (2015) reported medians ranging from <0.01 ppm – 0.04 ppm in green homes.…”
Section: Resultscontrasting
confidence: 67%
“…They found concentrations ranging from 2,000 to 56,000 count/cm 3 for indoor air in schools of the Cincinnati metropolitan area. Indoor total VOC levels measured in this investigation were fairly low compared to other studies conducted in the north-eastern US [210 – 6,000 μg/m 3 (Pickett et al, 2011)]. The indoor formaldehyde measurements also revealed somewhat lower levels than those reported by other investigators; Frey et al (2014) reported a median of 0.04 ppm in non-renovated homes and 0.05 ppm in renovated homes and Xiong et al (2015) reported medians ranging from <0.01 ppm – 0.04 ppm in green homes.…”
Section: Resultscontrasting
confidence: 67%
“…Although the EPA does not regulate indoor PM, these four PM statistics are within the monitor manufacturer's "action recommended for sensitive groups" or "action recommended" concentration ranges (Pickett & Bell, 2011). Re-sults of 21-day in-home air sampling showed that at the 50th percentile, the 152 homes with air sampling measurements had respirable ("Dust Control Handbook, OSHA," 2013) PM at an overall concentration of 14.0 µg/m 3 or less, and a highest 24-hour daily average concentration of 27.0 µg/m 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Pollutants present in the house air, mainly in industrialized countries, may damage the health of babies, since they spend most of their time within the same environment. Infant health may be affected by long-term exposure to NO 2, formaldehyde and black smoke (13) . Another risk associated with the intra and peridomestic quality of air found in this research was the emission of hydrogen sulphide gas by the cesspit tank.…”
Section: The Bedroom Is Closed Hot and Dark If There Was A Window mentioning
confidence: 99%